Psychosomatic status parameters and cardiovascular remodeling in patients with arterial hypertension - A. V. Shabalin; E. N. Gulyaeva; O. V. Kovalenko; S. V. Myshkin; E. M. Verkoshanskaya (Кардиоваскулярная терапия и профилактика, 2005)
The review is devoted to the role of psychosomatic status factors in the development of pathological cardiovascular remodeling in essential arterial hypertension. Cell mechanisms of left ventricular hypertrophy, cardiovascular risk factors’ influence on its progression are analyzed in detail.